Peningkatan Keterampilan Menulis Karangan Narasi Dengan Metode Mind Mapping Pada Siswa Kelas IV SD Negeri 2 Seren - Widiawati, Dede; Khairiyah, Puput; Ratnaningsih, Arum (Innovative: Journal Of Social Science Research, 2025)
This research aims to improve the narrative writing ability of fourth grade students at SD Negeri 2 Seren through the Mind Mapping method. This method was chosen because it can help students organize ideas visually, thus making the writing process easier, especially in narrative essay writing material. This research uses a classroom action research (PTK) approach with two cycles. Each cycle consists of planning, implementation, observation and reflection stages. Data was collected through observation, narrative writing tests, and interviews. The research results show that the Mind Mapping method significantly increases students' ability to write narrative essays. Students find it easier to design story lines, enrich vocabulary, and compose sentences. Thus, this method is effective to be applied as a learning strategy for narrative writing at the elementary school level.